2015
DOI: 10.1039/c5sc00584a
|View full text |Cite
|
Sign up to set email alerts
|

Rh-catalyzed decarbonylation of conjugated ynones via carbon–alkyne bond activation: reaction scope and mechanistic exploration via DFT calculations

Abstract: In this full article, detailed development of a catalytic decarbonylation of conjugated monoynones to synthesize disubstituted alkynes is described. The reaction scope and limitation has been thoroughly investigated, and a broad range of functional groups including heterocycles were compatible under the catalytic conditions. Mechanistic exploration via DFT calculations has also been executed. Through the computational study, a proposed catalytic mechanism has been carefully evaluated. These efforts are expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 67 publications
0
26
0
1
Order By: Relevance
“…4 Recently, we reported the Rh-catalyzed decarbonylation of diynones and mono-ynones enabled by using bidentate phosphine ligands with a large bite angle (Scheme 1, eqs 1 and 2). 5 DFT calculations supported an initial cleavage of the alkynyl acyl bond for these transformations. Given the unique nature of this bond cleavage, it is natural to wonder if such a mode of activation can be extended to other systems, such as 1,2-diketones.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…4 Recently, we reported the Rh-catalyzed decarbonylation of diynones and mono-ynones enabled by using bidentate phosphine ligands with a large bite angle (Scheme 1, eqs 1 and 2). 5 DFT calculations supported an initial cleavage of the alkynyl acyl bond for these transformations. Given the unique nature of this bond cleavage, it is natural to wonder if such a mode of activation can be extended to other systems, such as 1,2-diketones.…”
mentioning
confidence: 78%
“…Hence, these reasons motivated us to investigate a controlled catalytic decarbonylation of alkynyl α-diketones. The challenges are twofold: 1) compared to other ketones, yn-α-diones exhibit significantly higher electrophilicity and can undergo facile cycloaddition 8 and intramolecular cyclization 9 ; thus, substrate stability and chemoselectivity are not trivial issues; 2) conjugated ynones, the product of mono-decarbonylation of yn-α-diones, were previously demonstrated to undergo facile decarbonylation to give 1,2-disubstituted alkynes, 5b thus, discovering a new catalytic system that can selectively halt at the mono-decarbonylation stage can be another concern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the successful CO extrusion research, Dong and co‐workers realized an elegant decarbonylation of diynones to produce 1,3‐diynes via Rh‐catalyzed carbon–carbon activation . The same group later extended the methodology to the formation of disubstituted alkynes from monoynones . With the use of a Rh/Xantphos catalytic system, the scope and limitations were thoroughly investigated, and a broad range of functionalities including heterocycles were compatible under the developed conditions (Scheme ).…”
Section: Carbon–carbon Bond Forming Reactionsmentioning
confidence: 99%
“…[38] The same group later extended the methodology to the formation of disubstituteda lkynes from monoynones. [39] With the use of aR h/Xantphos catalytic system,t he scope and limitations weret horoughly investigated, and ab road range of functionalities including heterocyclesw ere compatible under the developed conditions (Scheme 25). Furthermore, mechanistic explorations by applying DFT calculations indicated that the Scheme21.…”
Section: Intramolecular Decarbonylation Of Ketonesmentioning
confidence: 99%